Microplastics from lagooning sludge to composts as revealed by fluorescent staining- image analysis, Raman spectroscopy and pyrolysis-GC/MS. (1st December 2020) - El Hayany, Bouchra; El Fels, Loubna; Quénéa, Katell; Dignac, Marie-France; Rumpel, Cornelia; Gupta, Vijay Kumar; Hafidi, Mohamed
Abstract: Lagooning sludge (LS), which is used as soil amendment in Morocco, may contain microplastics (MPs). The aim of this study was to examine the effect of dewatering and co-composting of LS with green waste (GW) on the MPs' evolution. In this context the present study proposes fast-preliminary steps to detect plastics in lagooning sewage sludge before the extraction and identification process. We used pyrolysis GC/MS spectrometry to investigate the presence of chemical compounds possibly derived from plastics, and fluorescence staining by Nile Red to detect fluorescent particles suspected as plastics. Thereafter, we quantified the MPs particles after density fractionation and investigated their nature by Raman spectroscopy. Results: indicated the presence of an average of 40.5 ± 11.9 × 10 3  MPs particles/kg (dry matter) and 36 ± 9.7 × 10 3  MPs particles/kg (dry matter) in fresh sludge and dewatered sludge respectively. Sludge dewatering in drying beds resulted a loss of small MPs (<500 μm). In co-composts, the quantity of MPs varied with the proportion of sewage sludge. The distribution of MPs types differentiated by colour and types (polypropylene, polyethylene, polyamide and polyester) evolved differently. Conventional co-composting did not have any effect on MPs quantity, indicating that they are not biodegradable under these temperature conditions, but it influenced their particle size. The risks of these pollutants after repeated field application and the possibility of their reduction through others co-composting procedures and techniques would be further investigated. Highlights: Lagooning sewage sludge contains considerable amount of microplastics. Small microplastics (<500 μm) are lost during sludge dewatering in drying beds. Co-composting did not reduce microplastics quantity but reduced the particle size. Co-composting leads to the physical degradation of plastics.